(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2022)
The worldwide expansion of digital labour platforms has a transformative impact on labour markets, reconfiguring employment relations and labour management both on a local and global scale. Lately, the growing literature on digital labour platforms is increasingly documenting how platform workers around the world are to a great extent migrants. Our article draws on data from empirical research on digital platforms providing housecleaning in Denmark, to emphasise how the intersection of migrant work, digital technologies, labour market regulations and migration law exacerbate inequalities and institutionalise precarious working conditions. We analyse platform housecleaning in Denmark through the lens of the “institutionalisation of precarity” and “Autonomy of Migration” concepts, to highlight that it is a phenomenon simultaneously co-constructed by migrants’ agency and structural factors. We conclude that critical studies on platform labour and future research should engage deeper with the intersecting realities (legal, social, gendered etc.) that shape migrant workers’ precarious lives, and migrants’ own strategies to navigate the shortcomings of exclusive and hostile labour market environments.